Development of emotional intelligence in students with special educational needs - Garbenis, Simas; Geležinienė, Renata; Šiaučiulytė, Greta (Social Welfare: Interdisciplinary Approach, 2020)
The aim of the study is to analyse teachers’ opinion about the development of emotional intelligence in students who have special educational needs in inclusive schools. The method of the questionnaire survey was chosen to achieve the research aim. The study employed two developed questionnaires based on the principle of Likert scale (1-5). The questionnaires were developed for teachers according to the parts of the structure of trait emotional intelligence for students aged 7 to 12 and 13 to 17 years. Questionnaires potentially reveal teachers’ opinion about several aspects of emotional intelligence development: how and how often teachers assess, organize targeted and non-targeted educational activities for individual parts of the structure of students’ emotional intelligence and promote awareness of their importance. After conducting the research, it was found that the development of parts of the structure of emotional intelligence was carried out differently depending on students’ age. Differences were recorded both between the developed parts of the structure and between applied educational activities. Both statistically significant and insignificant research data were obtained and it was found that the development of emotional intelligence for younger students was more oriented to their inner self-knowledge; while for older students, to the aspects of socialization.